The Last Great American Picture Show New Hollywood Cinema in the 1970s - King, Noel; Elsaesser, Thomas; Horwath, Alexander (Film Culture in Transition, 2004)
The Last Great American Picture Show brings together essays by scholars and writers who chart the changing evaluations of the American cinema of the 1970s, sometimes referred to as the decade of the lost generation, but now more and more recognized as the first New Hollywood, without which the cinema of Francis Coppola, Steven Spielberg, Robert Zemeckis, Tim Burton or Quentin Tarantino could not have come into existence. Identified with directors such as Sam Peckinpah, Arthur Penn, Peter Bogdanovich, Monte Hellman, Bob Rafelson, Hal Ashby, Robert Altman and James Toback, American cinema of the 1970s is long overdue for this re-evaluation. Many of the films have not only come back from oblivion, as the benchmark for new directorial talents. They have also become cult films in the video shops and the classics of film courses all over the world.